Bacillus megaterium GEB3 reduces accumulation of reactive oxygen species and enhances drought tolerance in peppers - Dongryeol Park; Jinwoo Jang; Geupil Jang (Applied Biological Chemistry)
Abstract Plant growth-promoting rhizobacteria regulate plant growth and stress tolerance by modulating endogenous developmental and physiological processes. This study examined the role of Bacillus megaterium GEB3 in affecting drought stress tolerance in peppers. GEB3 treatment significantly mitigated drought-induced symptoms, such as chlorosis, wilting, and leaf rolling, in both vegetative- and reproductive-stage peppers. For example, GEB3 treatment increased the number of fruits and total fruit weight by approximately 34% and 68%, respectively, compared to those in untreated control plants. We observed that GEB3 treatment reduces drought-induced reactive oxygen species (ROS) accumulation while increasing the transcriptional expression of antioxidant genes encoding peroxidases and superoxide dismutases, which are responsible for ROS removal. Furthermore, GEB3 activated the jasmonic acid (JA) response, and JA treatment alone was sufficient to reduce the accumulation of ROS and enhance pepper tolerance to drought stress. These findings suggest that Bacillus megaterium GEB3 increases drought tolerance in peppers through JA-mediated suppression of ROS accumulation, and may serve as a promising bioinoculant for improving crop tolerance against environmental stresses including drought.